2003
DOI: 10.1177/112067210301300709
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus: A Risk Factor Affecting Visual Outcome in Branch Retinal Vein Occlusion

Abstract: The VA 1 year after BRVO in patients with diabetes is worse compared to the VA in patients without diabetes. The VA stabilizes 1 year after onset in both groups. Diabetic patients tend to need more frequent follow-up in order to treat the sequelae of BRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Previously, largestudiesusing hospital-basedcontrols have shown an increased risk of RVOinpatients with hypertension, diabetes mellitus, atherosclerosis and hypercholesterolemia (6)(7)(8)(9)(10)(11)(12)(13)(14).Literature on associated thrombophilic abnormalitiesin varioustypes of RVOhas accumulated over the years,predominantlybased on retrospectiveretrievalofinformation from case records of variable numbers of patients seen in routine clinical practice ( 15). Prospective studieso nt his subjecth owever are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, largestudiesusing hospital-basedcontrols have shown an increased risk of RVOinpatients with hypertension, diabetes mellitus, atherosclerosis and hypercholesterolemia (6)(7)(8)(9)(10)(11)(12)(13)(14).Literature on associated thrombophilic abnormalitiesin varioustypes of RVOhas accumulated over the years,predominantlybased on retrospectiveretrievalofinformation from case records of variable numbers of patients seen in routine clinical practice ( 15). Prospective studieso nt his subjecth owever are rare.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,22 However, Swart et al observed that BRVO patients having diabetes had a worse visual acuity as compared to patients without diabetes. 23 Fifteen out of 40 (37.5 %) patients had diabetes in the current study. Salomon et al showed hyperlipidemia as a risk factor for BRVO.…”
Section: Discussionmentioning
confidence: 58%
“…It is noteworthy that our findings of worse visual outcome have been corroborated in a small study reporting a mean VA of 20/63 in 28 diabetic eyes compared with 20/40 in 49 nondiabetic eyes at 1 and 2 years, although the primary treatment modality was grid-pattern laser. 14 In our study, the number of injections that diabetic eyes required at 1 year is slightly higher than anti-VEGF treat-asneeded regimens for ranibizumab and bevacizumab. In a review of 21 eyes with BRVO on a treat-as-needed protocol with intravitreal ranibizumab, the average baseline VA was 20/72.…”
Section: Brvo Outcomes In Diabeticsmentioning
confidence: 52%